Correlation Between Urea and Phosphate Reduction Ratios During Hemodialysis - Begum, Maryam; Arshad, Abdul Rehman (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the efficacy of serum phosphate and urea removal during hemodialysis.Study Design:  Correlational Cross-sectional study.Place and Duration of Study: Combined Military Hospital, Peshawar, Pakistan from Jul to Dec 2020.Methodology: Adult patients on maintenance hemodialysis for three months or more were selected by non- probability convenience sampling. Exclusion criteria included hemodialysis for acute kidney injury, the initial three sessions of maintenance hemodialysis in patients with end-stage renal disease and patients unwilling for inclusion in the study. All patients had blood samples collected for serum urea and phosphate before and immediately after completion of hemodialysis session using standard technique. Urea and phosphate reduction ratios were calculated and compared by linear regression.Results: Hemodialysis sessions were monitored in 76 patients, including 54(71.05%) males and 22 (28.95%) females having mean age of 53.38±13.82 years. During the three-and-a-half-hour-long sessions, urea reduction ratio was greater than phosphate reduction ratio (70.14±11.60% vs 53.19±13.17% respectively). There was a moderate statistically significant correlation between the two (r=0.23; p=0.009). The urea reduction ratio was dependent on gender but not on type of vascular access. Phosphate reduction ratio was not dependent on gender or vascular access.Conclusion: Phosphate reduction is not as effective as urea reduction during hemodialysis. Thus, other modalities are required for better control of serum phosphate levels amongst patients undergoing hemodialysis.